Can Taxes and Bonds Finance Government Spending? - Stephanie Bell (Levy Economics Institute of Bard College, 1998)
This paper investigates the commonly held belief that government spending is normally financed through a combination of taxes and bond sales. The argument is a technical one and requires a detailed analysis of reserve accounting at the central bank. After carefully considering the complexities of reserve accounting, it is argued that the proceeds from taxation and bond sales are technically incapable of financing government spending and that modern governments actually finance all of their spending through the direct creation of high-powered money. The analysis carries significant implications for fiscal as well as monetary policy.
Keywords: 330